Plant Innate Immunity Multicomponent Model - Andolfo, Giuseppe; Ercolano, Maria R. (Frontiers in Plant Science, 2015)
Our understanding of plant–pathogen interactions is making rapid advances in order to address issues of global importance such as improving agricultural productivity and sustainable food security. Innate immunity has evolved in plants, resulting in a wide diversity of defence mechanisms adapted to specific threats. The postulated PTI/ETI model describes two perception layers of plant innate immune system, which belong to a first immunity component of defence response activation. To better describe the sophisticated defence system of plants, we propose a new model of plant immunity. This model considers the plant’s ability to distinguish the feeding behaviour of their many foes, such as a second component that modulates innate immunity. This hypothesis provides a new viewpoint highlighting the relevance of hormone crosstalk and primary metabolism in regulating plant defence against the different behaviours of pathogens with the intention to stimulate further interest in this research area.